(untitled) (Per Musi, 2015)
Mapping of significant institutions using music as an important aesthetic and pedagogical element in the social transformation of citizens in Salvador (Brazil), a city that, far from tourist appeal, presents considerable poverty rates, concentration of income and socioeconomic inequality. The theoretical framework is grounded in critical geography and the concept of ecology of knowledge. The chosen methodology includes the collection and analysis of Salvador´s official socioeconomic statistics, and a field research with application of semi-structured interviews.